Variation of wood properties within a dominant and suppressed tree of tamarack (Larix laricina (Du Roi) K. Koch) - Wong, Jean K. (My University, 1987)
Radial and axial variations of tracheid length, specific gravity, ring width, and latewood percentage were studied from the stems of a dominant and a suppressed tamarack tree. The trees were 81 and 83 years old respectively, grown in a natural stand near Thunder Bay, Ontario. Specimens were taken from every other ring from the pith to bark along the south and north aspect, at heights 0.15, 1.5, 4.5, 7.5, 10.5, 13.5, and 16.5 m in the tree stems. Juvenile wood and mature wood in the stem were distinguished by using the variation pattern of tracheid length as the criterion. In the mature wood of the dominant and suppressed trees, the average tracheid lengths were 3.16 mm and 2.96 mm, specific gravities 0.48 and 0.45, ring widths 1.09 mm and 0.85 mm, and latewood percentages 36.7% and 35.1% respectively. In the juvenile wood of the two trees, the average tracheid lengths were 2.11 and 2.10 mm, specific gravities 0.48 and 0.44, ring widths 2.36 mm and 1.97 mm, and latewood percentages 29.7% and 33.1% respectively. At all heights sampled, tracheid length increased radially from the pith outward, and leveled off at a certain ring age towards the bark. The rate of increase in tracheid length with ring age increased with height. The ring age at which tracheid length started to level off was used as the boundary of the juvenile and mature wood. The ring age of the boundary decreased with increasing height. Average tracheid length of the juvenile and mature wood increased axially from the base upward, reaching a maximum at the 4.5 m height, then decreasing to the top. Specific gravity and latewood percentage increased radially from the pith outward in the juvenile wood for most of the heights, while they fluctuated in the mature wood. Specific gravity and latewood percentage varied axially without a definite pattern with increasing height in the dominant tree, and they decreased upward in the suppressed tree. Ring width decreased radially from the pith outward in the juvenile wood, and fluctuated in the mature wood. Axially, the ring width decreased with increasing height slightly in the mature wood, and it increased in the juvenile wood with height from the 1.5 m height upward, reaching a maximum at the 4.5 to 7.5 m heights, and then decreasing to the top. The difference between the south and north aspect was not significant in tracheid length and ring width. Specific gravity and latewood percentage was significantly higher in the south than north aspect. The dominant tree on average had significantly higher values of tracheid length, specific gravity, and ring width than the suppressed tree.
Keywords: Wood; Tamarack; Tracheid length; Specific gravity; Latewood percentage